PSYCHOLOGICAL CHARACTERISTICS OF GAME ACTIVITY IN CHILDREN - Maxkambayeva Shaxrizoda Xusan qizi (European Journal of Humanities and Educational Advancements, 2023)
The article discusses the psychological impact of the external environment on the organization of play activities in children. This article gives a brief overview of the importance of play in a child’s life, the types and characteristics of play activities, and the benefits of playing games. It also explores the possibility of gaining a scientific understanding by covering the psychological effects of the game